LITERASI TOLERANSI BERAGAMA DAN BERBUDAYA BAGI REMAJA DI RUMAH TAHFIZH (YTPQ) CENTER PADANG PANJANG: Tolerance Literacy of Religious and Culture for Youth at Rumah Tahfizh (YTPQ) Center Padang Panjang - Hijratur Rahmi; Melisa Fitri Rahmadinata; Septriani Septriani (ASOSIASI IDEBAHASA KEPRI, 2023)
The younger generation is the cornerstone of the nation's successor who will lead the direction in which the achievement of the nation's goals will be directed. As a country full of diversity of customs, ethnicities, nations and beliefs, literacy of tolerance really needs to be instilled so that the younger generation can respect one another. The Institute of Indonesia Art Padang Panjang team took the initiative to collaborate in building a tolerant young generation's mental attitude by providing training activities to them, especially in West Sumatera. On this occasion, the team conducted this training activity at one of the Tahfizh Qur'an Padang Panjang by means of material and discussion. This activity was carried out for three meetings with sub-themes of activities; 1) Religious Tolerance According to Islamic Shari'a 2) Equality in religion and culture and 3) religious and cultural communication. The background of this activity is the importance of building a religious and cultured mentality in accordance with the Minangkabau aforism “Adat Basandi Sarak, Sarak Basandi Kitabullah”. The method of this training activity is carried out by means of interactive material training and discussion. The results of this activity indicate that Tahfizh Quran youth are interested in the activities carried out and are active in discussions. Teenagers understand the concept of tolerance and indirectly apply this awareness in their daily lives. Evaluation is carried out by responding to various case phenomena presented by the speaker.